Foundations and Donations as a Link Between Croatia and the Dalmatian Cities in the Early Middle Ages - Budak, Neven (2005)
The author analysis a number of charters and other early medieval documents from Dalmatia, which reveal the links established between the Croatian elite and the Dalmatian towns through means of pious donations and foundations.